To add, subtract, multiply or divide two functions from graph, we have to perform the same arithmetic operation with the outputs of the function f(x) and g(x). Let us see this briefly.
Let the given functions as f(x) and g(x).
Adding functions :
(f + g)(x) = f(x) + g(x)
Let (x, a) and (x, b) be the coordinates in the function f(x) and g(x) respectively. To add these two functions, we follow the rule following.
(f + g)(x) ==> (x, a + b)
Subtracting functions :
(f - g)(x) = f(x) - g(x)
Let (x, a) and (x, b) be the coordinates in the function f(x) and g(x) respectively. To subtract these two functions, we follow the rule following.
(f - g)(x) ==> (x, a - b)
Multiplying functions :
(f ⋅ g)(x) = f(x) ⋅ g(x)
Let (x, a) and (x, b) be the coordinates in the function f(x) and g(x) respectively. To multiply these two functions, we follow the rule following.
(f ⋅ g)(x) ==> (x, a ⋅ b)
Dividing functions :
(f / g)(x) = f(x) / g(x)
Let (x, a) and (x, b) be the coordinates in the function f(x) and g(x) respectively. To multiply these two functions, we follow the rule following.
(f / g)(x) ==> (x, a / b)
Use the graphs of f and g to evaluate the functions.
Problem 1 :
a) (f + g)(3) b) (f/g)(2)
Solution:
(f + g)(3) = f(3) + g(3)
= 2 + 1
(f + g)(3) = 3
b) (f/g)(2)
Solution:
(f/g)(2) = f(2)/g(2)
= 0/2
(f/g)(2) = 0
Problem 2 :
a) (f - g)(1) b) (fg)(4)
Solution:
(f - g)(1) = f(1) - g(1)
= 2 - 3
(f - g)(1) = -1
b) (fg)(4)
Solution:
(fg)(4) = f(4) ⋅ g(4)
= 4 ⋅ 0
(fg)(4) = 0
Problem 3 :
a) (f ∘ g)(2) b) (g ∘ f)(2)
Solution:
(f ∘ g)(2) = f[g(2)]
= f(2)
(f ∘ g)(2) = 0
b) (g ∘ f)(2)
Solution:
(g ∘ f)(2) = g[f(2)]
= g(0)
(g ∘ f)(2) = 4
Problem 4 :
a) (f ∘ g)(1) b) (g ∘ f)(3)
Solution:
(f ∘ g)(1) = f[g(1)]
= f(3)
(f ∘ g)(1) = 2
b) (g ∘ f)(3)
Solution:
(g ∘ f)(3) = g[f(3)]
= g(2)
(g ∘ f)(3) = 2
Use the graphs of f and g to solve.
Problem 5 :
Find (f + g)(-3)
Solution:
(f + g)(-3) = f(-3) + g(-3)
= 4 + 1
= 5
Problem 6 :
Find (g - f)(-2).
Solution:
(g - f)(-2) = g(-2) - f(-2)
= 2 - 3
= -1
Problem 7 :
Find (fg)(2)
Solution:
(fg)(2) = f(2) ⋅ g(2)
= -1 ⋅ 1
= -1
Problem 8 :
Find (g/f)(3)
Solution:
(g/f)(3) = g(3)/f(3)
= 0/-3
= 0
Problem 9 :
Draw the graph of of f + g and find domain and range.
Solution:
So, the domain of (f + g) is (-4, 3).
Problem 10 :
Find the domain of f/g.
Solution:
x -5 -4 -3 -2 -1 0 1 2 3 4 5 |
f(x) undefined 5 4 3 2 2 1 -1 -3 undefined undefined |
g(x) -1 0 1 2 2 1 1 1 0 -1 -2 |
f/g undefined undefined 4 1.5 1.5 2 1 -1 undefined undefined undefined |
So, the domain of (f/g) is (-3, 2).
Problem 11 :
Graph f + g.
Solution:
x -5 -4 -3 -2 -1 0 1 2 3 4 5 |
f(x) undefined 5 4 3 2 2 1 -1 -3 undefined undefined |
g(x) -1 0 1 2 2 1 1 1 0 -1 -2 |
f+g undefined 5 5 5 4 3 2 0 -3 undefined undefined |
Problem 12 :
Graph f - g.
Solution:
x -5 -4 -3 -2 -1 0 1 2 3 4 5 |
f(x) undefined 5 4 3 2 2 1 -1 -3 undefined undefined |
g(x) -1 0 1 2 2 1 1 1 0 -1 -2 |
f-g undefined 5 3 1 0 1 0 -2 -3 undefined undefined |
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM